KEMAMPUAN MEMBACA PERMULAAN AKSARA LONTARAK SISWA KELAS III SDN NO. 204 INPRES BALANG KABUPATEN TAKALAR - Febrianty, Ine; Yunus, Andi Fatimah; AJ, Andi Agussalim (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
The aim of this research is to describe the initial reading ability of the lontarak script of class III students at SDN NO. 204 Balang Presidential Instruction, Takalar Regency. This type of research is quantitative research in the form of quantitative descriptive. The population in this study were all class III students at SDN NO. 204 Inpres Balang, totaling 19 people, is only in 1 class. The sample determined was 19 students, using a saturated sampling technique. The data collection technique used is a test technique, namely an oral test. The data collected will be analyzed using descriptive statistical techniques. The results showed that the ability to read the beginning of the lontarak script of class III students at SDN No. 204 Balang Presidential Instruction Takalar Regency is declared incapable. This can be seen from the percentage of students who obtained a score ≥ 75 in the capable category that did not reach the set criteria, namely 75%, but only achieved 42.1%.